Relationship between type of smokeless tobacco & risk of cancer: A systematic review - Gupta, Sanjay (Indian J Med Res, 2018)
BACKGROUND & OBJECTIVES: Causative linkages of smokeless tobacco (SLT) use with oral potentially malignant disorders and cancers of oral cavity, oesophagus and pancreas have been reported. Published meta-analyses have provided pooled risk estimates for major cancers caused by SLT, both on global and regional levels. This systematic review was aimed at summarizing the available studies on occurrence and mortality risk of common cancers due to various SLT products. METHODS: PubMed and Google Scholar databases were systematically searched from 1985 till January 2018 for observational studies on SLT and cancer. The included studies were evaluated and data were extracted and reviewed. RESULTS: The review included 80 studies providing 121 risk estimates for various cancers. Majority of the studies from South-East Asian Region (SEAR) and Eastern Mediterranean Region (EMR) showed a significant positive association of SLT use with oral [odds ratio (OR) ranging from 1.48 to 27.4] and oesophageal cancers (OR between 2.06 and 12.8), while studies from European Region (EUR) reported a positive association with pancreatic cancer (OR between 1.6 and 2.1). Cancer-related mortality was evaluated in a few reports with higher risk of mortality for lung (OR between 2.0 and 9.1), cervical (OR 2.0) and prostate (OR 2.1) cancers. A wide variation was noted in the association of various cancers and specific SLT products based on their nature, methods of use and inherent toxicity. The majority of chewing tobacco products displayed higher risk for oral and oesophageal cancers while the same was not observed for snus. INTERPRETATION & CONCLUSIONS: This review emphasizes on the significantly positive association of SLT use with oral and oesophageal cancers in SEAR and EMR and pancreatic cancer in EUR. Mortality estimates for SLT-associated cancers need further analysis. Risk analysis for cancers of other sites in SLT users also requires multicentric well-designed studies.